Factors Affecting Brand Loyalty At Hotpot Restaurant In Jakarta - Keni Keni; Stephanie Clarissa (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2024)
This research aims to indicate whether social media marketing, brand experience and brand image predict brand loyalty for hotpot restaurants in Jakarta, directly or indirectly, from a customer engagement perspective. One hundred forty-five respondents were consumers of hotpot restaurants in Jakarta, who distributed questionnaires online, collected data using a Likert scale, and processed it with Smart-PLS. The results show that social media marketing, brand image and customer engagement can positively and significantly indicate brand loyalty. Meanwhile, brand experience cannot positively predict brand loyalty. Finally, social media marketing and brand experience can indicate customer engagement positively and significantly. Social media marketing and brand experience can positively and significantly mediate brand loyalty. From these results, researchers hope that hotpot restaurant management can increase business competitiveness and create accurate marketing strategies to create satisfaction and the desire to enjoy the restaurant.